Antitrypanosomatid Pharmacomodulation at Position 3 of the 8‐Nitroquinolin‐2(1H)‐one Scaffold Using Palladium‐Catalysed Cross‐Coupling Reactions. (17th September 2018) - Pedron, Julien; Boudot, Clotilde; Bourgeade‐Delmas, Sandra; Sournia‐Saquet, Alix; Paloque, Lucie; Rastegari, Maryam; Abdoulaye, Mansour; El‐Kashef, Hussein; Bonduelle, Colin; Pratviel, Geneviève; Wyllie, Susan; Fairlamb, Alan H.; et al.
Abstract: An antikinetoplastid pharmacomodulation study at position 3 of the recently described hit molecule 3‐bromo‐8‐nitroquinolin‐2(1 H )‐one was conducted. Twenty‐four derivatives were synthesised using the Suzuki–Miyaura cross‐coupling reaction and evaluated in vitro on both Leishmania infantum axenic amastigotes and Trypanosoma brucei brucei trypomastigotes. Introduction of a para ‐carboxyphenyl group at position 3 of the scaffold led to the selective antitrypanosomal hit molecule 3‐(4‐carboxyphenyl)‐8‐nitroquinolin‐2(1 H )‐one (21 ) with a lower reduction potential (−0.56 V) than the initial hit (−0.45 V). Compound 21 displays micromolar antitrypanosomal activity (IC50 =1.5 μm ) and low cytotoxicity on the human HepG2 cell line (CC50 =120 μm ), having a higher selectivity index (SI=80) than the reference drug eflornithine. Contrary to results previously obtained in this series, hit compound 21 is inactive toward L. infantum and is not efficiently bioactivated by T . brucei brucei type I nitroreductase, which suggests the existence of an alternative mechanism of action. Abstract : Para ‐sites against parasites : Antikinetoplastid pharmacomodulation at position 3 of an 8‐nitroquinolin‐2(1 H )‐one scaffold was achieved using an optimised Suzuki–Miyaura cross‐coupling reaction. Among the 24 molecules synthesised, a para ‐carboxyphenyl derivative was identified as a new selective antitrypanosomal hit with a lower reduction potential. Unlike the initial hit, this compound is not efficiently bioactivated by type I trypanosomal nitroreductase, which suggests an alternative mechanism of action.